FANATISME SUPORTER SEPAK BOLA TERHADAP PERILAKU AGRESI - Anindya Wiralarasati; Chelsea Gita Kharisma; Muhammad Nanda; Sofyan Hutamam; M.Delvin Oknanda (Journal of Communication and Social Sciences, 2023)
The development of the sports world is currently running very fast and the growth of the sports industry is accompanied by an increase in the number of followers. Many fans watch football. The large number of soccer fans is because soccer is a sport that is very popular with all groups, both children and adults. an overly enthusiastic attitude towards a point of view or problem. This attitude may be based on his thoughts and understandings, which do not change or remain the same. According to Winston Churchill, "bigotry is that which cannot change either the mind or the topic of conversation." The feeling that someone who is excited cannot change his mind or change the subject. Aggression is an act of harm that is detrimental by a person/institution/group against another person/institution/group. This type of research is quantitative correlative. The two variables involved in this research are bigotry as the independent variable and aggressive behavior as the dependent variable.